2018
DOI: 10.1098/rsos.180744
|View full text |Cite
|
Sign up to set email alerts
|

Telomeres as integrative markers of exposure to stress and adversity: a systematic review and meta-analysis

Abstract: Telomeres have been proposed as a biomarker that integrates the impacts of different kinds of stress and adversity into a common currency. There has as yet been no overall comparison of how different classes of exposure associate with telomeres. We present a meta-analysis of the literature relating telomere measures to stresses and adversities in humans. The analysed dataset contained 543 associations from 138 studies involving 402 116 people. Overall, there was a weak association between telomere variables an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 57 publications
5
56
2
Order By: Relevance
“…Although it is clear that telomere length is substantially heritable, perhaps accounting for as much as 70% of the variance in telomere length (Broer et al, 2013;Hjelmborg et al, 2015), such estimates clearly leave room for environmental effects. In fact, despite substantial genetic influence on telomere length before birth, twin studies indicate that environmental factors are the dominant source of influence across the life span (Bakaysa et al, 2007), a finding consistent with a recent meta-analysis linking exposure to stress and adversity with shorter telomeres (Pepper, Bateson, & Nettle, 2018).…”
Section: Hypothesis 1: Effects Of Adversity On Telomeressupporting
confidence: 74%
“…Although it is clear that telomere length is substantially heritable, perhaps accounting for as much as 70% of the variance in telomere length (Broer et al, 2013;Hjelmborg et al, 2015), such estimates clearly leave room for environmental effects. In fact, despite substantial genetic influence on telomere length before birth, twin studies indicate that environmental factors are the dominant source of influence across the life span (Bakaysa et al, 2007), a finding consistent with a recent meta-analysis linking exposure to stress and adversity with shorter telomeres (Pepper, Bateson, & Nettle, 2018).…”
Section: Hypothesis 1: Effects Of Adversity On Telomeressupporting
confidence: 74%
“…Leucocyte telomere length (LTL)—the length of the repeated TTAGGG sequence at the end of leucocyte chromosomes—is an extensively studied biomarker of human health and well-being. In support of a link between poorer health and shorter average LTL, many cross-sectional studies have found an association between tobacco smoking and shorter LTL [1,2]. Since human telomeres shorten with age, these data are widely interpreted as demonstrating that smoking accelerates the rate of biological ageing [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate with some concrete numbers, according to our simulations, repeatability of the TS ratio should be about 0.80 with error σ values of 0.05, 0.51 with error σ values of 0.1, and 0.28 with error σ values of 0.15. A widespread conclusion when surveying the qPCR telomere epidemiology literature is that there is a great deal of heterogeneity between studies [29,30]. Our findings suggest that small differentials in errors in the laboratory would be sufficient to drive large heterogeneity in outcomes.…”
Section: Discussionmentioning
confidence: 74%